Community dynamics and the lower airway microbiota in stable chronic obstructive pulmonary disease, smokers and healthy non-smokers. Issue 9 (4th May 2016) - Einarsson, G G; Comer, D M; McIlreavey, L; Parkhill, J; Ennis, M; Tunney, M M; Elborn, J S
Abstract : Rationale: The role bacteria play in the progression of COPD has increasingly been highlighted in recent years. However, the microbial community complexity in the lower airways of patients with COPD is poorly characterised. Objectives: To compare the lower airway microbiota in patients with COPD, smokers and non-smokers. Methods: Bronchial wash samples from adults with COPD (n=18), smokers with no airways disease (n=8) and healthy individuals (n=11) were analysed by extended-culture and culture-independent Illumina MiSeq sequencing. We determined aerobic and anaerobic microbiota load and evaluated differences in bacteria associated with the three cohorts. Culture-independent analysis was used to determine differences in microbiota between comparison groups including taxonomic richness, diversity, relative abundance, 'core' microbiota and co-occurrence. Measurement and main results: Extended-culture showed no difference in total load of aerobic and anaerobic bacteria between the three cohorts . Culture-independent analysis revealed that the prevalence of members of Pseudomonas spp. was greater in the lower airways of patients with COPD; however, the majority of the sequence reads for this taxa were attributed to three patients. Furthermore, members of Bacteroidetes, such as Prevotella spp., were observed to be greater in the 'healthy' comparison groups. Community diversity (α and β) was significantly less in COPD compared with healthy groups. Co-occurrence of bacterial taxa and the observation of a putative 'core' community within the lower airways were also observed. Conclusions: Microbial community composition in the lower airways of patients with COPD is significantly different to that found in smokers and non-smokers, indicating that a component of the disease is associated with changes in microbiological status.